SUBSTANTIATION OF NON-WASTE TECHNOLOGY USE OF FRUIT CITRUS MAXIMA - Darya Sergeevna Davidenko; Liliya Viktorovna Naymushina; Irina Dementieva Zykova (Современная наука и инновации, 2022)
The results of a study of biologically active substances (BAS) of the pomelo - Citrus Maxima, of the component composition of peel and zestessential oils, antioxidant activity of aqueous extracts of fruit different parts are presented.The scheme of rational use of pomelo fruit is proposed, which includes the production of essential oils, manufacture of candied peel from the skin, gettingjelly products from the pulp, the use of films-partitions as an additive to animal feed.